Uma abordagem para identificação de domínios de aplicação em ambiente de convergência digital - Venceslau, Amanda Drielly Pires (2013)
The emergence of the Interactive Digital Television provided, as well as advantages gain quality and optimization of the transmission, the addition of new features and services available to the user. With the advent of digital convergence between TV and Web platforms, new proposals of semantic organization of content are developed. Moreover, it was possible to introduce concepts of the Semantic Web and knowledge representation that allow semantically describe the metadata of content through ontologies. In this context, this work proposes an approach to identifying of domain of application in digital convergence environment based on the Semantic Web concepts and analysis of lexical and semantic similarity. One component integrated with Knowledge TV platform, was implemented to validate the approach.